Failure Mechanism Identification of Hook Components in Automatic Machines Using Visual and Material Analysis - Rahmawati, Nabila Desy; Lutiyatmi, Lutiyatmi (JMPM (Jurnal Material dan Proses Manufaktur), 2025)
The hook component in automatic packaging machines frequently experiences premature failure, leading to increased downtime, higher maintenance costs, and reduced production efficiency. This study aims to identify the failure mechanism of the hook through visual inspection, maintenance data analysis, and material characterization. Visual examination was performed on the fractured hook specimens to identify fracture morphology and surface characteristics. Historical maintenance records from 2017 to 2024 were analyzed to identify the frequency and type of failure. Chemical composition testing was performed using Optical Emission Spectroscopy (OES), while Rockwell hardness testing (HRC) evaluated the material’s mechanical properties. The results indicate that the hook failed through a brittle fracture mechanism, characterized by flat, granular fracture surfaces and the absence of plastic deformation. The primary failure factor was the direct impact between the hook and the punch, which occurred due to mechanical misalignment caused by bearing wear. The material, classified as medium carbon steel with 0.599 wt.% C and 1.000 wt.% Mn, exhibited high hardness but low toughness, leading to a brittle fracture under impact loading. Surface hardening followed by light tempering and shot peening is recommended to improve wear resistance and toughness, thereby reducing the risk of brittle fracture.